Suluk adalah Konsep Suluk Dalam Perspektif Syekh Akbar Muhammad Fathurrahman: Pengertian Suluk, Tahapan-Tahapan Suluk, Suluk Dalam Pemikiran Syekh Akbar Muhammad Fathurrahman, Relevansi Suluk dalam Kehidupan Modern - Nurfadila, Annisa; Bella Pili, Salim; Deni, Asep (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the Mosque Prosperity Movement (GAMIS) as a formulation of modern Sufism in the thoughts of Sheikh Akbar Muhammad Fathurahman within the Idrisiyyah Order. Sufism is understood not only as a process of spiritual development and purification of the soul through tazkiyah an-nafs, dhikr, and moral development, but also as a form of social service that provides benefits for the community. The concept of suluk developed by Sheikh Akbar emphasizes that the spiritual journey is not separate from social life, but must be realized in concrete actions oriented towards service and community empowerment. This study uses a qualitative descriptive method through field observations, in-depth interviews, and literature studies. The results show that GAMIS positions the mosque as a center of spiritual, educational, social, and economic activities that build individual and collective piety. Sufi values ​​such as sincerity, modesty, love, service, trust, and patience are implemented through activities such as daily suluk, charity, congregational character development, and community empowerment programs. Thus, GAMIS is a modern, adaptive and contextual model of Sufism, which is able to integrate spiritual and social aspects harmoniously, and provides a real contribution to the revitalization of the function of mosques and strengthening community life in the contemporary era.